Aerospace series. Heat resisting alloy FE-PM1708. Vacuum arc remelted. Hardened and tempered. Bars. a or D ≤ 200 mm. 1 000 MPa ≤ Rm ≤ 1 140 MPa. (4th March 2020) - British Standards Institution,
No abstract available